Three-year Performance of Acacia auriculiformis Provenances at Serdang, Malaysia - Ab Shukor, Nor Aini; Awang, Kamis; Venkateswarlu, Perugupalli; Senin, Abd Latib (Universiti Putra Malaysia Press, 1994)
A trial consisting of 28 provenances ofAcacia auriculifonnis A. Cunn. ex Benth. was measured for survival and growth at 6, 12, 18, 24 and 36 months. Tree form was also assessed at 18 months. Of the provenances, 7 were from northern Queensland and 15 from Northern Territory, Australia, and 6 from Papua New Guinea. All provenances survived well (> 66%) but they differed significantly (P < 0.01) in their growth performance after 6 months. Half of the provenances tested had more than 50% of their trees with single stems. Queensland provenances generally grew faster than those from Northern Territory and Papua New Guinea. For timber production, four Queensland provenances (Archer River, Coen River, Wenlock River and Kings Plain), three Northern Territory provenances (Noogoo Swamp, Douglas River and E. Alligator River), and a Papua New Guinean provenance (Old Tonda Village) were identifzed as promising.